Climate Change and Security: South Asia - Mannan, Farzana (The Jahangirnagar Review Part-C, 2024)
One of the biggest challenges to global peace and security in the twenty-first century is climate change. This research article seeks to appraise the security risks that climate change may pose to South Asia, more specifically Bangladesh, India and Pakistan. It looks at the climate change scenario of South Asian countries, particularly Bangladesh, India and Pakistan and analyses through the lenses of two theoretical frameworks: a) human security approach and b) conventional security approach. It claims that the effects of climate change increase the human insecurities of the people of South Asian countries as most of them are dependent on natural resources for their livelihoods. These human insecurities lead them to migrate, most often internally. But there is a possibility of cross-border migration to the neighbouring countries due to climate change, notwithstanding the fact that migration is already there for other reasons – for example, as economic migrants, as refugees and so on. This, in turn may increase border tension between and among the countries. This research also claims that climate change may compound the water sharing issues of transborder rivers of South Asia and may create potential traditional security problems.